The first recorded case of herbicide resistance in Estonia: common chickweed (Stellaria media) resistant to sulfonylureas - Silvia Pihu; Andres Mäe; Hannah Joy Vivian Kennedy; Katerina Hamouzova (Agricultural and Food Science)
Herbicide resistance has been insufficiently studied in the Baltic countries. Chickweed (Stellaria media), an adaptive and competitive annual weed, poses a significant agricultural threat due to its low and dense canopy. This study aimed to evaluate the level of resistance to acetolactate synthase (ALS) inhibitors in chickweed populations in Estonia and identify potential mechanisms. In the initial dose-response experiment, a biotype from Järva County exhibited resistance to the ALS inhibitor tribenuron-methyl. Molecular analysis identified a mutation at position 574 in the ALS gene, where tryptophan was replaced by leucine. Testing of eight chickweed biotypes for resistance to tribenuron-methyl and the combination herbicide iodosulfuron + amidosulfuron found three resistant biotypes. The Järva County biotype was cross-resistant to sulfonylureas, while two others exhibited resistance only to iodosulfuron + amidosulfuron. The latter two biotypes lacked the ALS gene mutation, suggesting non-target-site resistance mechanisms, although these were not investigated further. These findings highlight the potential for widespread herbicide resistance in Estonia and emphasize the need for more comprehensive monitoring and research into resistance mechanisms.